Kletva i pokušaj zaštite od kletve u pripoveci „Kumova kletva” Janka Veselinovića - Kostić, Ljiljana (Wydawnictwo Naukowe UAM, 2013)
In his rural themed short stories, Janko Veselinović gave snippets of life in the Serbian village of the XIX century that represent a valuable material for ethnological study. Folk meditations on sin, punishment, oath, damnation etc. were often the driving force behind his short stories. The subject of our work is Veselinović’s short story The Godfather’s Curse where the author wanted to depict the way in which a curse, just like in the beliefs of the ancients, strike the one who had committed a sin. No one can escape the curse, not even the strongest ones, nor their descendants, because in the short stories by Janko Veselinović evil must be punished.
The Curse and the Attempt to Protect from the Curse in the Short Story "The Godfather’s Curse" by Janko Veselinović
Keywords: Janko Veselinović; rural themed short story; curse; godfather’s curse; damnation